Oceanographic variability and its influence on pelagic fish catch in the Bali Strait - Abu Bakar Sambah; Trisnanda Devi Oktavia; Denny Wijaya Kusuma; Fenni Iranawati; Nurin Hidayati; Adi Wijaya (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2020)
The existence of pelagic fish resources is greatly influenced by the condition of the waters which are described through its relationship with the oceanographic parameters. As a dominant species in Bali Strait, lemuru fish (Sardinella lemuru) have catch dynamics that vary each year. Oceanographic factor influence the number of fish catch in Bali Strait, in which global phenomena such as ENSO and IOD also have a role in influencing the migration of marine resources. This research aims to analysis annual variation of Sea Surface Temperature (SST) and Sea Surface Chlorophyll-a (SSC) in Bali Strait, and its effect on fish catch. The method applied a quantitative descriptive with correlation analysis and spatial analysis using Geographical Information System approach. The analysis described a significant impact of oceanographic parameters on pelagic fish catch. SSC has a significant impact on the number of fish catch which describes a positive correlation, and it illustrated a time interval between the highest concentration of SSC and the period of fishing peak season. It also impacts the fishing trip and the distribution of fishing ground that spread along the area of the Indian Ocean to Bali Strait. SSC has a significant impact on the number of fish catch which describes a positive correlation, and it illustrated a time interval between the highest concentration of SSC and the period of fishing peak season. It also impacts the fishing trip and the distribution of fishing ground that spread along the area of the Indian Ocean to Bali Strait